PSORIASIS TREATMENT IN PEDIATRIC AGE – PART II: PHOTOTHERAPY AND SYSTEMIC TREATMENT - Maria João Cruz; Sofia Magina; Teresa Boudrier; Filomena Azevedo (Journal of the Portuguese Society of Dermatology and Venereology, 2011)
Psoriasis is a chronic inflammatory disorder, multisystem and immunologically mediated. Approximately one third of adults refer the age of onset before 16, representing about 4% of all dermatoses seen in pediatric age. The majority of cases are mild and adequately managed with topical medications. A minor subset of children present with severe, rapidly evolving disease that requires systemic therapy. The use of these therapies is limited by the risk of toxicity, the low acceptance and lack of studies to validate and guide the use of most of these drugs in children. This is the second of two articles which aim to review the topical (Part I) and systemic (PartII2) treatment options available, as well as its safety and efficacy in children.